PERAN SELF-ESTEEM TERHADAP SELF-DISCLOSURE PADA PENGGUNA AKUN ALTERNATIF INSTAGRAM The Role of Self-Esteem in Self-Disclosure Among Alternative Instagram Account Users - Christy Tiya Angelene Br.Sitorus; Nuriyatul Lailiyah (Interaksi Online, 2026)
This study is grounded in the growing phenomenon of alternative Instagram accounts—private secondary accounts used as a more personal space for self-expression—which have become increasingly common among Generation Z university students yet remain underexplored from a psychological perspective. A mixed methods approach was employed with emphasis on qualitative inquiry, combining a preliminary survey of 35 Communication Science students at Diponegoro University (class of 2022) with in-depth interviews involving 5 selected informants. Data were analyzed through open coding, axial coding, and selective coding stages. Drawing on Rosenberg's (1965) theory of self-esteem and Jourard's concept of self-disclosure, this study aims to understand the role of self-esteem in students' self-disclosure on alternative Instagram accounts. The findings reveal that self-esteem operates not as a static variable but as a contextual and audience-responsive condition. On primary accounts with broad and heterogeneous audiences, informants' self-esteem was more vulnerable due to fear of social judgment, resulting in more controlled, defensive, and curated self-expression; several informants admitted to having deleted posts after publishing them. On alternative accounts, where audiences had been carefully filtered and consisted primarily of trusted close contacts, self-esteem was more stable, enabling freer, more spontaneous, and more authentic self disclosure. Fear of judgment served as a limiting factor on primary accounts, while the sense of safety from a trusted audience functioned as a catalyst for openness on alternative accounts. Social support in the form of likes, story replies, and appreciation from followers strengthened informants' self-esteem, which in turn encouraged greater self-disclosure. This pattern forms a mutually reinforcing dynamic: stable self-esteem drives self-disclosure; positive responses generate social validation; and social validation further strengthens self-esteem. This study affirms that self-esteem functions as a psychological factor that comprehensively shapes students' self-disclosure patterns and that the creation of alternative accounts represents a deliberate psychological adaptive strategy by Generation Z students.